Patients’ perspectives on determinants avoidable hospitalizations - Sarmento, João (2022)
Funding Information: We thank Centro Hospitalar de Lisboa Central for helping to conduct the study, and the patients that participated in the study. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.